Preventive Efforts of Aqidah Akhlak Teachers in Addressing Student Delinquency at Madrasah Tsanawiyah Nururrodhiyah, Jambi City - Mohammad Alghazali Putra Kesuma, Nasir (Lembaga Bale Literasi, 2025)
This study investigates the preventive efforts of Aqidah Akhlak teachers in addressing student delinquency at MTs Nururrodhiyah Jambi City. Employing a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving the school principal, Aqidah Akhlak teachers, and grade IX students. The findings reveal that most students have internalized positive moral values, though a minority continued to engage in delinquent behaviors, including smoking, truancy, tardiness, fighting, and classroom disruption. The Aqidah Akhlak teacher implemented multidimensional preventive strategies encompassing professional self-development, enrichment of pedagogical knowledge, enhancement of teaching skills, reinforcement of student discipline, motivational guidance, and systematic awareness-raising regarding the consequences of delinquency. Supporting factors include teacher certification pathways, a conducive school environment, and adequate facilities, while inhibiting factors involve qualification mismatches, limited monitoring of external social environments, and insufficient family reinforcement. By the conclusion of the study, repeat incidents of delinquency had declined markedly among grade IX students, affirming the significant role of the Aqidah Akhlak teacher in Islamic character education.